Efektivitas Pendidikan dan Pelatihan Teknis Petugas Lapangan Keluarga Berencana Kota Jambi - Suwardi Suwardi (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2018)
The research is based on the increasing target and level of achievement of work plans for family planning or Keluarga Berencana (KB) field officers, so that education and training are needed to improve their competencies. This study aims to look at the effectiveness of technical education and training in family planning field training in improving the quality of family planning services in Jambi City. The study was conducted in qualitative method and data was collected through observation, interviews and documentation. Based on the research that has been done, it is found that 1) education and training for family planning field officers is a program that aims to increase capacity and knowledge so that services to the community increase, 2) there are still many field workers who have not received education and training in program services KKBPK, 3) coverage of the task area is still limited and transportation is minimal.